How Transformational Leadership and Job Satisfaction Can Effect on Organizational Commitment and Increase Organizational Citizenship Behavior - Yuliantini, Tine; Ramli, Muhammad; Kuswibowo, Christian; Malihah, Fadhila Dhia; Ali, Anees Janee (Universitas Mercu Buana, 2024)
Objectives. Businesses are obligated to have high-quality personnel. In the face of technological advances and business competition, organizations need to raise the standard of their resources and and raising the standard of resources is shown by the commitment in the organization and organizational citizenship behavior (OCB).Methodology: This study method involved with the quantitative method and using (SEM) analysis with software (PLS). In this study, there was a population of 50 employees and the sampling technique is saturated sampling with 50 sample.Finding:. The Result are transformative leadership involves significant and positive transformational leadership has an impact on the dedication of the organizationsignificant and positive impact on OCB, job contentment has a significant and positive impact on organizational, Organizational dedication and fulfillment at work both significantly and favorably affect OCB.Conclusion:To increase OCB in an organization, supporting factors such as transformational leadership, job satisfaction and organizational commitment within the institutional environment